Two forms of activation-induced cytidine deaminase differing in their ability to bind agarose. - Mirjam Metzner (PLoS ONE, 2010)
Activation-induced cytidine deaminase (AID) is a B-cell-specific DNA mutator that plays a key role in the formation of the secondary antibody repertoire in germinal center B cells. In the search for binding partners, protein coimmunoprecipitation assays are often performed, generally with agarose beads.We found that, regardless of whether cell lysates containing exogenous or endogenous AID were examined, one of two mouse AID forms bound to agarose alone.These binding characteristics may be due to the known post-translational modifications of AID; they may also need to be considered in coimmunoprecipitation experiments to avoid false-positive results.